2006
DOI: 10.1126/science.1123775
|View full text |Cite
|
Sign up to set email alerts
|

The Embryonic Vertebrate Heart Tube Is a Dynamic Suction Pump

Abstract: The embryonic vertebrate heart begins pumping blood long before the development of discernable chambers and valves. At these early stages, the heart tube has been described as a peristaltic pump. Recent advances in confocal laser scanning microscopy and four-dimensional visualization have warranted another look at early cardiac structure and function. We examined the movement of cells in the embryonic zebrafish heart tube and the flow of blood through the heart and obtained results that contradict peristalsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
222
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 253 publications
(228 citation statements)
references
References 8 publications
5
222
1
Order By: Relevance
“…3A,B, Supplementary Movies 1 and 2; n ϭ 10). In parallel studies, we have explored the nature of this pumping and found that it is not due to peristalsis but, instead, results from the impedance mismatches that are present between the inflow tract, the outflow tract, and the heart tube, creating a suction pump (Forouhar et al, 2006). By 33 hpf, heart looping has begun (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3A,B, Supplementary Movies 1 and 2; n ϭ 10). In parallel studies, we have explored the nature of this pumping and found that it is not due to peristalsis but, instead, results from the impedance mismatches that are present between the inflow tract, the outflow tract, and the heart tube, creating a suction pump (Forouhar et al, 2006). By 33 hpf, heart looping has begun (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have also shown that even at the heart tube stage, pumping efficiency is highly sensitive to changes in heart beat frequency with temperature, suggesting that such valveless pumping may not be suitable for postembryonic circulation (Forouhar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The heart begins as a linear tube of myocardium lined with endocardial cells that functions like a suction pump (Forouhar et al, 2006), but quickly loops and grows into a fourchambered heart complete with valves and septa that pumps in a piston manner. This process involves several key events that happen in three dimensions, including linear heart tube looping, septation of the ventricles, and development of the atrioventricular (AV) valve apparatus, defects in which result in a myriad of clinically relevant congenital heart defects (Collins-Nakai and McLaughlin, 2002;Gittenberger-de Groot et al, 2005).…”
Section: Introductionmentioning
confidence: 99%